2011
DOI: 10.1371/journal.pone.0025059
|View full text |Cite
|
Sign up to set email alerts
|

Homozygosity Mapping on Homozygosity Haplotype Analysis to Detect Recessive Disease-Causing Genes from a Small Number of Unrelated, Outbred Patients

Abstract: Genes involved in disease that are not common are often difficult to identify; a method that pinpoints them from a small number of unrelated patients will be of great help. In order to establish such a method that detects recessive genes identical-by-descent, we modified homozygosity mapping (HM) so that it is constructed on the basis of homozygosity haplotype (HM on HH) analysis. An analysis using 6 unrelated patients with Siiyama-type α1-antitrypsin deficiency, a disease caused by a founder gene, the correct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…We and others have shown that the autozygome approach can be very effective in guiding the mutation analysis (Aldahmesh et al 2009;Pomares et al 2010). Interestingly, this approach was also used successfully in populations where consanguinity is uncommon (Hildebrandt et al 2009;Collin et al 2011;Hagiwara et al 2011;Schuurs-Hoeijmakers et al 2011). However, this approach has its limitations.…”
Section: Autozygome/exome Analysis In Retinal Dystrophymentioning
confidence: 99%
“…We and others have shown that the autozygome approach can be very effective in guiding the mutation analysis (Aldahmesh et al 2009;Pomares et al 2010). Interestingly, this approach was also used successfully in populations where consanguinity is uncommon (Hildebrandt et al 2009;Collin et al 2011;Hagiwara et al 2011;Schuurs-Hoeijmakers et al 2011). However, this approach has its limitations.…”
Section: Autozygome/exome Analysis In Retinal Dystrophymentioning
confidence: 99%
“…13 Although homozygosity mapping has been focused primarily on inbred affected individuals, recent advances potentially provide a basis for homozygosity mapping in affected individuals who are not inbred. [14][15][16][17][18] Deleterious recessive variants in such individuals might reside in smaller ROH than in inbred individuals, but in ROH nonetheless. Increased density of genotype data has enabled the detection of increasingly smaller ROH, thereby reducing the level of inbreeding required for subjects examined in homozygosity-mapping studies.…”
Section: Introductionmentioning
confidence: 99%
“…Increased density of genotype data has enabled the detection of increasingly smaller ROH, thereby reducing the level of inbreeding required for subjects examined in homozygosity-mapping studies. [14][15][16][17][18] In these studies, however, the fact that patterns of homozygosity, including ROH patterns, are influenced not only by the locations of recessive-disease loci, but also by population history and consanguinity levels, is a major consideration.…”
Section: Introductionmentioning
confidence: 99%
“…We used homozygosity fingerprinting to obtain the identity by descent (IBD). 12 Exome sequencing was performed using 2 samples from patients, 1-IV-2 and 2-IV-1 (figure 1A), as previously described. 13 More than 100,000 variants in each sample were called.…”
Section: Patientsmentioning
confidence: 99%